2020
DOI: 10.3389/fpsyg.2020.566965
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Support Protects Lonely People Against COVID-19 Anxiety: A Three-Wave Longitudinal Study in China

Abstract: The isolation necessary to prevent the spread of the coronavirus disease 2019 (COVID-19) can give rise to anxiety, especially for lonely people who often feel upset without others' company. Although isolated from others, people can still receive support from others, which might lower their COVID-19 anxiety. To examine the relationship between loneliness, perceived social support, and anxiety, we measured 222 Chinese participants' (54.50% female, M age = 31.53, SD = 8.17) trait loneliness, chronic anxiety befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
95
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 52 publications
11
95
1
3
Order By: Relevance
“…The COVID-19 pandemic has not only increased people's anxiety but also reduced their SWB (Kachanoff et al, 2020;Qiu et al, 2020;Rosen et al, 2020;Xu et al, 2020). SWB represents people's appraisals and evaluations of their own lives (Diener et al, 2018).…”
Section: Covid-19 Pandemic Increases Anxiety and Lowers Swbmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic has not only increased people's anxiety but also reduced their SWB (Kachanoff et al, 2020;Qiu et al, 2020;Rosen et al, 2020;Xu et al, 2020). SWB represents people's appraisals and evaluations of their own lives (Diener et al, 2018).…”
Section: Covid-19 Pandemic Increases Anxiety and Lowers Swbmentioning
confidence: 99%
“…As a massive global crisis, the COVID-19 pandemic threatens people's mental health and gives rise to mental illness (Ettman et al, 2020;Fabian et al, 2020;Kachanoff et al, 2020;Qiu et al, 2020;Rosen et al, 2020;Tull et al, 2020;Xu et al, 2020). Previous cross-sectional studies showed that mental health (i.e., well-being) and mental illness (i.e., anxiety) were related but distinct phenomena (Keyes, 2005;Keyes et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The negative outcomes of loneliness on mental health during the pandemic were also observed in a sample of older adults, where perceived loneliness predicted COVID-19 related anxiety [7]. Furthermore, a longitudinal study on Chinese population found that trait loneliness had an impact on COVID-19 related anxiety [14].…”
Section: Psychological Factors Explaining Covid-19 Anxietymentioning
confidence: 76%
“…Furthermore, social isolation, especially among the elderly, leads to lower health care utilisation, which produces poorer health status [ 48 ]. Perceived social support protects lonely people, and this has become more evident during the COVID-19 pandemic [ 49 ]. EUROASPIRE-7 study, conducted across 27 European countries, found that social isolation and low level of education were associated with various cardiovascular risk factors [ 50 ].…”
Section: Discussionmentioning
confidence: 99%